Implementation of Character Culture in School Management Smp Negeri 5 Binjai - Sempurna; Rusli; Handoko (Rahis Cendekia Indonesia, 2023)
Character culture is an important pillar today in forming a good person. By instilling character in the process of teaching and learning activities to students can support the learning system more easily and effectively. Implementation of character in school management is a way for the situation in the school to run optimally with an interesting and conducive atmosphere. The character of school management has become something very important for teachers in the world of education, especially when teachers in the school nurture students. The implementation of character culture in school management is not only in the form of school settings, physical facilities and routines but also makes students' attitudes more characterful such as inculcating an attitude of independence, mutual cooperation, mutual respect, honesty, and others. By inculcating the character of school management, it is hoped that it can ease the task of teachers to get maximum results in increasing the effectiveness of learning. The research that the author conducted was a qualitative research taking the background of SMP Negeri 5 Binjai. The subject of this research is the implementation of the management character culture of SMP Negeri 5 Binjai. Data was collected by interview, observation and documentation study. Data analysis was carried out by qualitative descriptive, namely by describing and analyzing all field data and then making conclusions. The results of this study are expected to provide input in the cultivation of student character culture in the application of school management.